Управління якістю товарів і послуг - Страшинська, Лариса Володимирівна (My University, 2006)
Конспект лекцій з дисципліни "Управління якістю товарів і послуг" маає допомогти студентам краще опанувати лекційний матеріал, поглибити вивчення теоретико-методичних основ курсу, привернути їхню увагу до основних положень тем. Lectures on the subject "Managing the quality of goods and services" maae help students better master the lecture material, to deepen the study of the theoretical and methodological foundations of course, to draw their attention to the main provisions of the order.
Keywords: сертифікація продукції; стандартизація; якість продукції; методи визначення рівня якості; міжнародні стандарти; product certification; standardization; quality of products; methods of determining the level of quality; international standards; кафедра маркетингу